Financial toxicity risk among adult patients undergoing cancer surgery in the United States: An analysis of the National Inpatient Sample. Issue 3 (24th June 2019) - Farooq, Ayesha; Merath, Katiuscha; Hyer, J. Madison; Paredes, Anghela Z.; Tsilimigras, Diamantis I.; Sahara, Kota; Mehta, Rittal; Wu, Lu; Cloyd, Jordan M.; Ejaz, Aslam; Pawlik, Timothy M.
Abstract: Background and Objective: Financial hardship occurring as a result of cancer treatment has been termed financial toxicity and is an established side effect of the cancer treatment. We investigated the risk of financial toxicity among patients undergoing surgery for gastrointestinal cancers. Methods: All uninsured and privately insured patients who underwent surgery for a gastrointestinal cancer were identified from the National Inpatient Sample. Publicly available government data were used estimate income, food expenditure, and average maximum out‐of‐pocket expenditure. Risk of financial toxicity was defined as health expenditure ≥ 40% of postsubsistence income. Results: Among the 78 545 patients in the analytic cohort, 73 305 individuals had private insurance while 5240 patients were uninsured. Overall median hospital charges were 58 651 (IQR: 37 912‐95 379). Approximately 90% of uninsured and 10% of privately insured patients were at risk of financial toxicity. At the subpopulation level, patients in the lowest income quartile, undergoing emergency surgery, black or hispanic individuals, and those undergoing surgery for esophageal or colon cancer were more likely to experience catastrophic costs following surgery ( P < .001). Conclusion: Approximately 9 in 10 uninsured and 1 in 10 privately insured patients with cancer were at risk of financial toxicity after the surgery. Targeted interventions are needed to provide financial protection to patients undergoing the cancer treatment.